Faktor Risiko Lingkungan Terhadap Stunting Pada Balita - Putri Nur Riani; Budiyono Budiyono; Nurjazuli Nurjazuli (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2023)
Background: Stunting is an obstacle to growth and development that occurs in children. Stunting is caused by many factors, namely poor care, limited access to health services, lack of consumption of nutritious food, lack of access to clean water, and poor environmental sanitation. From several previous studies there have been various results regarding environmental factors that affect stunting but are still inconsistent and comprehensive. Therefore, this study is to analyze the environmental risk factors for stunting in toddlers more comprehensively.Methods: This research uses the literature review approach method. Articles come from journal databases including Science Direct, Scopus, EBS cohost, Cambridge Core, Proquest, EMBASE, Nature, E- Prints, E- Prints2, E-Catalog, Research Gate, SSRN, JSTOR, IGI Global, ASCE, Springer Link, Emerald Insight, Oxford Journals, Clinicalkey, Semantic Scholar, Pubmed, Arxiv, Garuda, Publons, Academia. Search results in the journal database obtained 590 articles about the environment, stunting, and toddlers with a vulnerable period of 10 years (2012 to 2022). The article obtained is designed for cross-sectional, case control and cohort research. Inclusion criteria such as duplication identification, title screening, abstract screening, and eligibility of full text articles obtained 14 articles corresponding to 9 articles in international journals and 5 articles in national journals.Result: The results of the 14 articles analyzed show that there is a relationship between environmental risk factors and stunting events in toddlers, environmental risk factors are a combination of several factors (multi-dimensional factors). The results of the study with cohort, case control, and cross sectional designs stated that poor WASH (Water, Sanitation, and Hygiene) interventions, water (inappropriate drinking water sources, drinking water treatment), sanitation factors (use of toilet facilities, open defecation behavior, disposal of toddler feces not in latrines), EED (environmental enteric dysfunction), children's habit of playing in agricultural land, pesticide exposure, washing sprayers, spraying, frequency and duration of diarrhea, frequency and duration of ARI are related to the incidence of stunting in toddlers. As for the cohort design, it states that environmental factors that influence stunting cases in toddlers are improper environmental sanitation, drinking water sources, and open defecation behavior.Conclusions:Â The severity of stunting cases in society is related and influenced by multidimensional factors, the most powerful environmental risk factors are factors of improper environmental sanitation, water infrastructure, and open defecation behavior (BABS), although it does not deny that there are other supporting factors such as ANC, Family economy, and exclusive breastfeeding.